Analysis of Gender Representation in Instagram Social Media Campaigns: A Case Study of the 2024 Central Java Gubernatorial Election - Ichza Ardiansya; Laila Kholid Alfirdaus (Universitas Medan Area, 2026)
This study examines gender representation in Instagram-based social media campaigns during the 2024 Central Java Gubernatorial Election. The research addresses the persistence of gender stereotypes in political communication, particularly in how the candidate pairs Andika Perkasa–Hendrar Prihadi and Ahmad Luthfi–Taj Yasin construct and communicate gendered messages through digital campaign content. This study employs a qualitative research design, employing textual, semiotic, and structural analyses. The data consist of 60 campaign posts collected through online observation from the official Instagram accounts of both candidate pairs during the campaign period. The collected posts were systematically coded and analyzed to identify recurring themes, visual symbols, and narrative patterns related to gender representation. The findings indicate that gender representation in the campaigns tends to reinforce traditional gender stereotypes. Male candidates are predominantly portrayed as strong, authoritative, and masculine leaders, while female representation remains limited and is often associated with supportive or domestic roles. Campaign communication strategies also rely heavily on masculine imagery to assert political authority. This study contributes to the literature on gender and political communication by demonstrating how digital campaign practices on social media may reproduce conventional gender norms in local electoral contexts, highlighting the need for more gender-inclusive political messaging in contemporary digital campaigns.